Pengelolaan Aset Wakaf Yayasan Badan Wakaf (YBW) Al-Ikhsan Kudus Untuk Anak Yatim - Amania, Naila (UIN Sunan Kudus, 2018)
This study aims to analyze the management of YBW Al-Ikhsan Kudus waqf assets for orphans. This type of research is field research with qualitative approach. Data collection techniques with observation, interview and documentation and data analysis are done inductively. The result of the study shows that the management of YBW Al-Ikhsan Kudus waqf assets is still consumptive and still has the potential to be productive. YBW Al-Ikhsan Kudus keep trying to produce waqf assets because some of the waqf assets that can produce have not been managed maximally by way of utilization of wakaf asset directly and indirectly. The opportunities and challenges of asset management of YBW Al-Ikhsan Kudus based on SWOT analysis are; S-O strategy, which is by optimizing the potential of waqf assets through the utilization of vacant land, cooperation with LKS, investment training nadzir, the formation of waqf savings. The S-T strategy, namely nadzir, must apply good management principles in the development of waqf assets. W-O strategy, that is with participation and active role wakif, nadzir, and foundation for empowering asset waqf. While the W-T strategy, namely by making the priority scale and innovation in empowering asset waqf.